PENGARUH PENDIDIKAN KESEHATAN BERBASIS EFIKASI DIRI TERHADAP PRILAKU MAHASISWI DALAM UPAYA DETEKSI DINI KANKER PAYUDARA DI STAI SYEKH H. ABDUL HALIM HASAN AL ISHLAHIYAH BINJAI TAHUN 2017 - Leny Suarni; Alam Bakti Keloko; Jenny Marlindawani Purba (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2018)
ABSTRACT Breast cancer is a serious and malignant threat often experienced by women including adolescents. Medical Records Data RSUD Dr RM Djoelham Binjai 2016 there are 20 cases ranging in age from 19-21 years 3 people (15%), and age 30- 65 years 17 people (85%). The type of research was quasi experiment. the design of pretest-posttest design with control group aims to determine the effect of self-efficacy based health education on knowledge, attitude, student action in the effort of early detection of breast cancer. Data analysis with Wilcoxon and Mann-Whitney Test with α = 0.05. Result of pretest mean rank of knowledge of treatment group 13,84 control group 19,16 with p = 0,106> 0,05, attitude of treatment group 13,56 control group 19,44 with p = 0,072> 0,05 action group treatment 15,25 group control 17,75 with p = 0,412> 0,05. Result of post-test mean rank knowledge of treatment group 23,81 control group 9,19 with p = 0,000 <0,05, attitude of treatment group 22,63 control group 10,38 with p = 0,000 <α0,05 and action group treatment 23,88 control groups 9,13 with p=0, 000 <0,05. There are differences in knowledge, attitudes and actions of students before and after self-efficacy based health education in the control group. It is suggested to Institution to improve student behavior by doing BSE every month, in the effort of early detection of breast cancer. Keywords: Health Education, Knowledge, Attitude, BSE Actions